Assessing information system performance in government agency from the user's perspective - Widyadomono, V. Mardi; WIjayanti, Lilis Endang; Pw, Kristianto; Rokhmat, Rokhmat (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
This study examines the factors influencing information system performance in government agencies in Sleman Regency, focusing on the user perspective. The user perspective needs to be analyzed, considering that in government organizations, there are sometimes information systems that have the same function but different usage instructions. Some information systems originate from the center and others are created independently by the regions. This causes operators to operate several systems that have almost the same function. The dependent variable is system performance, while the independent variables include personal technical skills, top management support, human resource quality, and education and training. Data were collected using questionnaires distributed to employees directly involved in the implementation and use of the information system. Out of 160 targeted respondents, 158 completed the questionnaire. The data were analyzed using linear regression, and hypotheses were tested with t-tests. The results show that all independent variables significantly affect information system performance, highlighting the importance of both personal and organizational factors in enhancing the effectiveness of information systems within government institutions.